The Efficiency of Fisheries Processing Industry in Indonesia Using Data Envelopment Analysis (DEA) - Anam, M. Khairul (Agrikan Jurnal Agribisnis Perikanan, 2021)
This study aims to determine the technical efficiency, allocative, cost and scale of the fisheries processing industry in Indonesia. The data used is cross-sectional data for the Indonesian Manufacturing Industry which was collected in the annual survey by the Central Statistics Agency/BPS Indonesia in 2017 registered with the KBLI’s code 10211 - 10219. Data envelopment analysis (DEA) is a nonparametric method in operations research and economics for boundary estimation production. It is used to measure the productive efficiency of the decision-making unit (DMU) empirically. The inputs to the fisheries production system are capital, labor, materials, land and energy. While the output is production. The results showed that West Sumatra, Lampung, West Java, East Java, Maluku and North Maluku had high efficiency values ​​in technical efficiency, but West Java and East Java were low in allocative efficiency and cost efficiency. However, nationally, the value of allocative efficiency and cost efficiency is still low. Therefore, all input efficiency still needs to be improved, in order to reduce production costs. In addition, the industry must make improvements by enhancing management capabilities and allocative efficiency.